Strata Data Superstream : Data Science Fundamentals - Croll, Alistair; Handy, Tristan; Odubela, Ayodele; Pelzel, Kristi; Dai, Jason; McRaney, David; Krishnamurthy, Venkat; Baden, Alex (O'Reilly Media, Inc., 2021)
Big data has been with us now for over 10 years, and in that time the tools and techniques have evolved. If youâ??re new to working with data or looking to understand the latest and greatest, these sessions are the perfect way to become part of the conversation. Youâ??ll learn how AI and the cloud have impacted how we grapple with ever-growing datasets and get better insight and products. About the Strata Data Superstream Series: This four-part series of half-day online events gives attendees an overarching perspective of key topics that will help your organization maximize the business impact of your data. What you'll learn-and how you can apply it Understand the problems the modern data stack helps solve today and get a glimpse of where weâ??re headed Get an overview of AI and machine learning and see how they can improve your data science work Learn how to present your data clearly and articulately This Superstream is for you because... You want to learn how data science works and understand its impacts, whether youâ??re swimming in data or just dipping in a toe. You need to know the trends in data workflows, techniques, and tools. Youâ??re interested in learning the role AI can play in your data analysis and want to find out where to start. You want to learn how to best present your data to outside stakeholders. Prerequisites: Come with your questions Have a pen and paper handy to capture notes, insights, and inspiration Recommend follow-up: Read Data Science from Scratch (book) Read Fundamentals of Data Visualization (book) Read Introduction to Machine Learning with Python (book).